The Convergence Of Internet And Radio In Turkey In The Perspective Of Distribution And Audience - Kuyucu, Mihalis (The Turkish Online Journal of Design Art and Communication, 2014)
The technological developments in the technology had effected media in different ways. It contributed radio, tv and print media which is called as traditional media’s distribution channels to be shaped again. From this effect radio has taken its role and new media has merged with radio which this has create a difference in both technologic and economic structure. In this paper, there has been done a research on the change of radio with the emergence that has with new media, it has underlined that radio has found the possibility to improve its power with that emergence. Listening to radio via internet has been increasing from day to day and the radio audience has found a possibility of listening to radio with the new distribution that this new technologic developments has created. This new form of listening radio has changed the interaction of the audience and radio station from one to two communication and this has caused radio stations to have better feedbacks and a two way communication with its audience. This two way communication has also contributed radio and new media’s meeting. Radio now can make sale of a service or product via e-commerce and can improve its economic power more than the past.
Keywords: Radio Broadcasting; Internet; e-commerce; Social Media; Media Researches; Radyo Yayıncılığı; İnternet; E-Ticaret; Sosyal Medya; Medya Araştırmaları